(untitled) (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: One of the most common congenital craniofacial defects in children is cleft lip and palate. Numerous challenges, including early feeding difficulties, nutritional problems, aberrant speech development, dental abnormalities, and hearing loss, are frequently present in them. Studies have revealed that kids with cleft lip and palate have delayed expressive language, which is demonstrated by their slower rate of sound and word acquisition with limited vocabulary. METHODOLOGY: A cross sectional survey was carried on 50 children with cleft deformity. Using google forms, a survey questionnaire was prepared using the Infant Toddler Checklist (ITC) assessing the communication skills of the children. Additional information was gathered about the family structure, number of languages, nuclear/joint family and the use of mobile phones. General physical examination and a growth evaluation were done. RESULTS: Among 50 children in the study, 30 children had normal total score corresponding to the age of the child whereas 20 children (40%) had low scores for the age of the child. 32% of children had a concern communication composite score, 30% of children had a concern expressive speech composite score whereas 38% of children had a concern symbolic composite score. CONCLUSION: Communication and language deficits are present in children with orofacial clefts. A comprehensive screening tool for communication delays in children between the ages of 6 and 24 months is called the ITC. Children who score positively on the screen or who have concerns on the ITC require additional testing for communication difficulties as well as an autism-specific screen.